Enhanced chemoprevention by the combined treatment of pterostilbene and lupeol in B[a]P-induced mouse skin tumorigenesis. (January 2017) - Singh, Payal; Arora, Deepika; Shukla, Yogeshwer
Abstract: The present study is aimed to evaluate the inhibitory effect of the combination of two phytochemicals; pterostilbeneand lupeol (generally obtained from blue berries, grapes, white cabbage, green pepper, olive and mangoes) on mouse skin tumorigenesis. We hypothesized that the concomitant topical treatment of selected phytochemicals would lead to improved impediment of skin cancer. Swiss albino mice (n = 25) received a topical dose of Benzo[a]pyrene (B[a]P, 5 μg/animal) with pre/post application of pterostilbene (16 μM/0.2 ml acetone/animal) and/or lupeol (500 μM/0.2 ml acetone/animal) for 32 weeks. Results showed that pterostilbene and/or lupeol treatment resulted in a significant delay in onset of tumorigenesis. However, a more promising effect on tumor suppression was noted with the combination of both the phytochemicals. A significant reduction in average tumor volume, cumulative number of tumors and tumor multiplicity was recorded in combination treated group. The histopathological analysis illustrated the marked suppression in epidermal hyperplasia and necrotic cells in combination treated groups. Our study suggests that the combination of pterostilbene and lupeol was more effective in prevention of skin cancer as compared to either of the phytochemical alone. Therefore, the combined treatment of phytochemicals has better potential to prevent skin carcinogenesis. Highlights: Phytochemicals (pterostilbene and lupeol) posses anticancerous effect in B[a]P skin cancer model. Combination of pterostilbene and lupeol enhances the chemopreventive effect. Phytochemicals combination provide better strategy to prevent skin carcinogenesis.